The Influence of E- Service Quality and Trust on E-Customer Loyalty Through Satisfaction for users of Grab Online Services in Medan City - Pasaribu, Lidya Natalia (ProBisnis : Jurnal Manajemen, 2023)
Objective study This is For analyze the influence of E - service quality and trust on E-customer loyalty through satisfaction user Grab online services in Medan City . The number of respondents in the research was 144 users of Grab online services in Medan City. The sampling technique used was Purposive Sampling with the Non-probability Sampling method. In accordance with data availability and analytical demands, researchers used SPSS version 24 to analyze the data. This research suggests that all variables have a significant influence between direct and mediated relationships starting from E-service quality and trust have a positive and significant influence on satisfaction, E-service quality and trust have a positive and significant influence on E-customer loyalty then Satisfaction has a positive and significant influence on E-customer loyalty. Furthermore, E-service quality and trust have an influence positive And significant towards E - customer loyalty through satisfaction user Grab online services in Medan City